Chylous effusions - Tomić Ilija; Plavec Goran; Karličić Vukojica; Spasić Vuleta; Rusović Siniša; Stanić Vojkan; Cvijanović Vlado; Ristanović Aleksandar (Vojnosanitetski Pregled)
This paper presents 4 patients with chylothorax, and one patient with bilateral chylothorax and chyloperitoneum. The chylous effusions were of benign etiology, developed as a complication of miliary tuberculosis (1 patient), after L-2 vertebral body fracture (1 patient), and idiopathic (2 patients). The diagnosis was confirmed by the presence of chylomicrons and high content of triglycerides in the effusion, ranged 11,9-29,1 mmol/l. Lymphangiography showed multiple abnormalites of lymphatic system, the obstruction of ductus thoracicus, dilatation and convulsion of lymphatic channels, but the site of lymphatic leak was not detected. The treatment included an extended period of pleural and peritoneal drainage with total parenteral nutrition (1 patient), pleurodesis using Corynebacterium parvum (2 patients), and surgical partial parietal pleurectomy with continous drainage (1 patient). The treatment was successful in all patients.